Tethered Particle Motion: an easy technique for probing DNA topology and transcription factor interactions - Kovari, Daniel T. (Methods Mol Biol, 2018)
Tethered Particle Motion (TPM) is a versatile in vitro technique for monitoring the conformations a linear macro-molecule, such as DNA, can exhibit. The technique involves monitoring the diffusive motion of a tracker particle anchored to a fixed point via the macro-molecule of interest, which acts as a tether. In this chapter, we provide an overview of TPM, review the fundamental principles that determine the accuracy with which effective tether lengths can be used to distinguish different tether conformations, present software tools that assist in capturing and analyzing TPM data, and provide a protocol which uses TPM to characterize lac repressor induced DNA looping. Critical to any TPM assay is understanding the timescale over which the diffusive motion of the tracker particle must be observed to accurately distinguish tether conformations. Approximating the tether as a Hookean spring, we show how to estimate the diffusion timescale, and discuss how it relates to the confidence with which tether conformations can be differentiated. Applying those estimates to a lac repressor titration assay, we describe how to perform a TPM experiment. Additionally, we also provide graphically driven software which can be used to speed up data collection and analysis. Lastly, we detail how TPM data from the titration assay can be used to calculate relevant molecular descriptors such as the DNA looping J factor and lac repressor – operator dissociation constants. While the included protocol is geared toward studying DNA looping, the technique, fundamental principles, and analytical methods are more general and can be adapted to a wide variety of molecular systems.